Chemical Modification of Petung Bamboo Fiber to Hybrid Composites: Modifikasi Kimia Serat Bambu Petung terhadap Komposit Hibrida - Yusron Maulana, Raden Muhammad; Rahma Rei Sakura; Nasrul Ilminnafik; Sumarji; Mahros Darsin (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
This study evaluates the effect of alkali treatment using NaOH solution on the mechanical properties and microstructure of hybrid composites based on epoxy resin reinforced with petung bamboo fiber and fiberglass. Bamboo fibers were immersed in five NaOH concentration variations (0%, 3%, 6%, 9%, 12%) before composite fabrication using the hand lay-up method. Tensile testing was performed according to ASTM D-638 standard and microstructural characterization using Scanning Electron Microscope (SEM). The results showed that 9% alkali treatment produced the best mechanical performance with a tensile strength of 58.68 MPa, elongation of 4.15%, and elastic modulus of 1413.49 MPa. SEM analysis indicated improved fiber-matrix adhesion due to removal of lignin and hemicellulose. Optimal alkali concentration enhanced composite performance, making it a potential candidate for eco-friendly vehicle interior applications.